Konsep Pentahelix Pada Pemberdayaan Usaha Mikro dan Kecil - Elvetta, Shisca; Murwadji, Tarsisius; Mulyati, Etty (Universitas Widya Gama Malang, 2024)
Empowerment according to Article 1 Number 8 of the MSME Law, is defined as an effort by the central government, regional governments, the business world, and the community in a synergistic manner. However, the fact that the implementation of the empowerment of digital micro and small enterprises (MSEs) in the marketplace by these stakeholders has actually become an inhibiting factor for the success of the programs carried out. As a result, the empowerment of the implementation program has not provided optimal results for the development and growth of digital MSEs in the marketplace. This research is based on a normative juridical approach and then analyzed by qualitative juridical methods. The specification of this research is analytical descriptive in order to describe the relationships between relevant stakeholders in providing support for the digital MSE empowerment program in the marketplace which is reviewed based on regulations and implementation in practice. The results of this study found that, first, the implementation of digital MSE empowerment in the marketplace by the government, the business world, universities, and communities is still partial and sectoral, resulting in overlapping programs. Second, the application of the Pentahelix concept to efforts to empower digital MSEs in the marketplace can be done by establishing the Pentahelix Institution, which is an entity that forms cooperative relationships between five stakeholders, consisting of the government, the business world, academia, the public, and the media. Furthermore, the formation of these institutions needs to be set forth in the form of laws and regulations.